A Little More Conversation A Little Less Prejudice: The Role of Classroom Political Discussions for Youth's Attitudes toward Immigrants. (4th May 2022) - Miklikowska, Marta; Rekker, Roderik; Kudrnac, Ales
ABSTRACT: Although previous research has shown that deliberative discussions have consequences for intergroup attitudes, very little is known about this impact during the formative adolescent years. In addition, the mechanism explaining the mechanism through which discussions affect intergroup attitudes is not clear. This 3-wave study of Swedish adolescents (N = 892, 51.1% girls, MageT1  = 13.41, nested in 35 classrooms) examined the role of teacher-initiated political discussions in the classroom for the development of youth attitudes toward immigrants. The results of multilevel analysis showed that adolescents who perceived political discussions to be less frequent increased in anti-immigrant attitudes compared to youth with more frequent discussions. Similarly, classrooms with less deliberative atmosphere were more negative toward immigrants than classrooms with a higher frequency of discussions, and this effect remained two years after the students moved to new schools. Mediation analysis revealed that general political interest (but not news consumption) explained the effects of classroom discussions on attitudes: Youth who perceived that their teachers frequently initiate political discussions developed higher general political interest and, in turn, lower anti-immigrant attitudes than youth with less frequent discussions. The findings show an important role of classroom political discussions for the formation of intergroup attitudes in adolescence. The findings suggest that frequent discussions reduce the risk of prejudice development by stimulating youth general political interest.